Communities with an anchor institution have higher coronavirus vaccination rates. Issue 1 (13th July 2022) - Harris, Alexandra; Maechling, Claude R.; Holl, Jane L.; McHugh, Megan
Abstract: Purpose: Anchor institutions ("anchors") are large employers, rooted in a community by reason of mission, capital, or relationships. Many anchors have encouraged coronavirus vaccination for employees and their families. Our objective was to determine whether the presence of an anchor was associated with a higher county‐level vaccination rate. Methods: A cross‐sectional study focused on 745 small‐ and mid‐sized US counties. We used data from the Centers for Disease Control and Prevention, Reference USA's US Business Database, Economic Innovation Group's Distressed Communities Index database, 2021 County Health Ratings and Rankings, 2020 US Presidential Election popular vote data, and National Center for Health Statistics urban‐rural classification data. We constructed 3 explanatory variables of interest: a binary variable indicating whether the county had an anchor; a continuous variable representing the number of anchors within a county; and the percent of all workers in the county who were employed by an anchor. Multivariable linear regression models were adjusted for race/ethnicity, political party allegiance, rurality, economic distress, and prevalence of smoking and adult obesity. Findings: Counties with an anchor had vaccination rates 2.31 ( P <.01) percentage points higher than those without an anchor. The number of anchors in a county was also significantly associated with higher vaccination rates. Conclusions: Efforts by anchors to encourage vaccination may have been successful, and that anchors may be well positioned to amplify public health messages. However, the influence and efforts of anchors to increase vaccination did not fully mitigate disparities in vaccination rates by race, ethnicity, and political party allegiance.